Defining putative glycan cancer biomarkers by MS. (October 2012) - Mechref, Yehia; Hu, Yunli; Garcia, Aldo; Zhou, Shiyue; Desantos-Garcia, Janie L; Hussein, Ahmed
For decades, the association between aberrant glycosylation and many types of cancers has been shown. However, defining the changes of glycan structures has not been demonstrated until recently. This has been facilitated by the major advances in MS and separation science, which allows the detailed characterization of glycan changes associated with cancer. MS glycomics methods have been successfully employed to compare the glycomic profiles of different human specimens collected from disease-free individuals and patients with cancer. Additionally, comparing the glycomic profiles of glycoproteins purified from specimen collected from disease-free individuals and patients with cancer has also been performed. These types of glycan analyses employing MS or LC–MS allow the characterization of native, labeled and permethylated glycans. This review discusses the different glycomic and glycoproteomic methods employed for defining glycans as cancer biomarkers of different organs, including breast, colon, esophagus, liver, lung, ovarian, pancreas and prostate.